PERILAKU DISTORSI, KEKERASAN DAN KOROSI HASIL HARDFACING PADA PERMUKAAN BAJA KARBON MENGGUNAKAN ELEKTRODA HV-800 DENGAN BERBAGAI KETEBALAN: Distortion, Hardness and Corrosion Behavior of Carbon Steel Hardfacing using HV-800 Electrodes with Various Thicknesses - Syaripuddin; Sopiyan; Ahmad Nur Hisyam; Rani Anggrainy (Universitas Negeri Jakarta, 2024)
This research aims to look at the hardness and corrosion of the weld layer. In addition, distortions were also observed in the post-welding specimens. Weld layers were made with variations of one, two and three layers of welding using HV-800 electrodes. The first step in this research is a literature study, followed by preparing tools and materials, heating electrodes, welding process, observing distortion, cutting specimens for testing followed by hardness and corrosion testing, and data analysis and conclusions. From the results of observing the distortion, it can be seen that the thicker the weld layer, the greater the distortion that will occur. Distortions in specimens welded with one, two and three layers are 1.5, 4 and 6° respectively. Furthermore, based on the results of the hardness test, it can be seen that the thicker the weld layer, the greater the hardness. The hardness of the one, two and three layer welded specimens was 550.2, 632.82 and 650.68 HV respectively. Then, based on the weighing results, it can be seen that the longer the immersion time, the greater the reduction in mass during 120 hours of immersing. Finally, from the results of the corrosion rate calculation it can be seen that the thicker the weld layer, the lower the corrosion rate that will occur. The corrosion rates for specimens welded with one, two and three layers were 13.23, 11.02 and 10.29 mpy, respectively. All three specimens have good corrosion resistance because they fall into the